Pandemic Induced E-Learning and the Impact on the Stakeholders: Mediating Role of Satisfaction and Moderating Role of Choice - Ganesh Dash (Athens Institute for Education and Research, 2023)
This study tries to assess the impact of e-learning on the stakeholders, especially teachers and students, and the differences. COVID-19, the current pandemic, is taken as the context. A structural equation modeling approach is undertaken, and PLS-SEM (partial least squares) (multi-group) method is chosen. Perceived Usefulness and Perceived Ease of Use are the independent constructs, with Behavioral Intention to Use being the dependent construct. Satisfaction is taken as a mediator, and Choice is used as a moderator. One hundred ninety-seven teachers and two hundred seventy-nine students comprise the sample. Results show that teachers' perceived usefulness has a significant and positive impact on their satisfaction. For both teachers and students, perceived ease of use has a significant and positive impact on behavioral intention. Satisfaction is a successful mediator for teachers but not for the students. Choice has proved to be a good moderator for the relationship between perceived ease of use and behavioral intention to use. The study is unique as a new moderator (choice) is introduced to the modified model, and in-depth analysis is conducted to assess the relationships and the differences between the two groups. Further, it is a multi-national study enhancing its universal implications.